Generating Compiled Simulations Using Partial Evaluation - Weise, Daniel; Seligman, Scott; Au, Wing-Yee (Partial Evaluation and Automatic Program Generation, 1991)
Using a program specializer, we automatically generated high-performance digital simulation algorithms from a simple interpreter-based simulator. By making simple changes in the simulator and the specializer, we generated four types of compiled simulations: the PC-set algorithm, an improvement on the PC-set algorithm, and two compiled versions of the BACKSIM algorithm. An analysis of our experiments indicate that large improvements to the PC-set method are possible, and that compiled simulation based on the pure BACKSIM algorithm should not be further investigated as the overhead of the algorithm is larger than the time it saves by pruning gate evaluations.